Association of allostatic load with functional disability in the China Health and Retirement Longitudinal Study - Zhao, Wanyu; Si, Yanjun; Li, Xueqin; Zhao, Yunli; Jia, Shuli; Dong, Birong (The Journal of nutrition, health & aging, 2024)
Allostatic load (AL) is an index that manifests as cumulative wear and tear on multiple physiological systems resulting from repeated adaptation to stressors throughout the life course. Higher AL was found to be associated with increased risk of adverse health outcomes, but studies on functional disability among large Chinese older population were limited. We aimed to investigate the associations of AL with functional disability among Chinese older adults. This prospective cohort study included 5880 older adults who were at least 50 years old and participated in the CHARLS at baseline (2011 wave), with 3 follow-ups (2013, 2015 and 2018 waves). We selected 11 biomarkers from 4 physiological systems to construct AL. AL score was classified into three categories based on tertiles: 0–1 (low burden), 2–3 (medium burden) and 4–11 (high burden). Functional disability was assessed by activities of daily living (ADL) and instrumental activities of daily living (IADL). Multivariable logistic regression models examined the association between baseline AL, transitions of AL burden and incidence of functional disability. In cross-sectional analyses, medium and high AL burden were associated with an increased prevalence of ADL disability, while association was only significant between high AL burden and IADL disability. During the 7-year follow-up, 1102 and 1777 participants incident ADL disability and IADL disability, respectively. Those with medium and high AL burden had an increased risk of new-onset ADL disability than those with low AL burden (“medium”: OR = 1.25, 95%CI = 1.01, 1.55; “high”: OR = 1.69, 95%CI = 1.32, 2.18). As for IADL disability, association was only significant in “high” group (OR = 1.50, 95% CI = 1.24, 1.83). We also found keep medium/high AL burden in 2011 and 2015 was associated with new-onset ADL (OR = 2.27, 95%CI = 1.50, 3.44) and IADL disability (OR = 1.51, 95%CI = 1.11, 2.05) in 2018. These results show that higher AL predicts functional disability among Chinese older adults. Monitoring AL and paying close attention to those with medium/high AL burden may aid prevention of adverse health outcomes, thus giving a healthier ageing experience to a large proportion of the population.